PENERIMAAN WARISAN HARTA SECARA BENIFISIER PERSPEKTIF HUKUM PERDATA - Dalimunthe, Dermina (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2019)
Inheritance that is received benifisier or determines a condition for the recipient of the inheritance is that if the testator has a debt in his life, the beneficiary only pays the heir's debt the amount of inheritance he receives, according to which the inheritance recipient does not bear the inheritor's debtÂ